HOTS Outcomes in IPAS Learning Through the Discovery Learning Model for Fifth Graders of SDN Sukamulya - Erlina Erlina; Levina Putri; Heryani Heryani; Ina Setiawati; Mia Zultrianti Sari; M. Deni Ruhiyat; Ilham Nur Ikhsan; Frian Sumarya (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2026)
This study addresses the low higher-order thinking skills (HOTS) among elementary students by evaluating the implementation of the discovery learning model. It aims to determine the science and social sciences (IPAS) learning outcomes of fifth-grade students at SDN Sukamulya, analyze their obstacles in solving HOTS questions, and identify factors influencing their HOTS development. Employing a descriptive quantitative approach, this study involved 20 fifth-grade students. Data were collected via HOTS-oriented essays and observations, then analyzed using descriptive statistics and a one-sample t-test against the Minimum Mastery Criterion (KKM = 75). The results showed a mean post-test score of only 46.75, significantly below the KKM, with only 5% of students achieving mastery. Most students fell into the "very low" HOTS category due to three main factors: limited teacher readiness in designing HOTS learning, lack of supporting learning media, and low student prior knowledge. In conclusion, these findings underscore the urgent need for systematic improvements in implementing discovery learning to effectively foster higher-order thinking skills at the elementary school level.